Programmer as Translator: The LHC of Chinese Artificial Intelligence Poetry. - Krenz, Joanna (Chinese Literature & Thought Today, 2025)
The paper considers artificial intelligence (AI) poetry as a case of specifically understood translation, namely the translation of a certain paradigm of poeticness upheld among Chinese society into virtual reality. It discusses three aspects of such a translation, including linguistic, human, and cultural factors, abbreviated as LHC by analogy to the Large Hadron Collider, in which dynamic and hardly predictable interactions between particles take place. In each of these spheres, the author traces the features of the conventional paradigm, the process of translation (coding and social engineering), and the inconspicuous but consequential paradigm slippages that appear underway. The analyzed material consists of algorithms and applications that generate classical-style poetry and manifestations of their presence in the public discourse, such as a television show featuring the best-known classical-style bot poets, Jiuge.